Identification and Functional Prediction of Circular RNAs Related to Growth Traits and Skeletal Muscle Development in Duroc pigs - Ma, Lixia; Chen, Wei; Li, Shiyin; Qin, Ming; Zeng, Yongqing (Frontiers in Genetics, 2022)
Porcine skeletal muscle is a highly heterogeneous tissue type, and the Longissimus Dorsi muscle (LDM), as the most economical and physiologically metabolized skeletal muscle in pigs, has always been the focus of research and improvement in pig molecular breeding. Circular RNA, as an important new member of regulatory non-coding RNA after microRNA, has become a frontier hot spot in life science research. This study aims to explore candidate circRNAs related to growth, meat quality and skeletal muscle development among Duroc pigs with different average daily gain (ADG). Eight pigs were selected and divided into two groups: H group (high-ADG) and L group (low-ADG), following with RNA-Seq analysis to identify circRNAs. The results showed that backfat at 6-7 rib (BF) and Intramuscular fat (IMF) content in H group was significantly lower than L group, but ribeye area (REA) in H group was higher than L group. In RNA-seq, 296 Differentially expressed (DE) circRNAs (157 upregulated and 139 downregulated) were identified and exons flanking long introns are easier to circularize to produce circRNAs. Most of DE circRNAs were enriched in Quantitative trait locus (QTL) regions related to meat quality and growth traits. In addition, a gene can produce one or more circRNA transcripts. It was also found that the source genes of DE circRNAs were enriched in MAPK, FoXO, mTOR, PI3K-Akt and Wnt signaling pathways. The results showed that different ADG, carcass and meat quality traits among half-sibling Duroc pigs with the same diet may be due to the DE circRNAs related to skeletal muscle growth and development.